2020
DOI: 10.3389/fmats.2020.588130
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Mechanical Strength of SAP Internally Cured Concrete

Abstract: To investigate the relationships between the different mechanical strengths of internally cured concrete with Super Absorbent Polymer (SAP concrete), the uniaxial mechanical properties of SAP concrete with different internal curing water-cement ratios were studied. Various SAP concrete specimens were prepared, and the uniaxial compressive, splitting tensile, as well as four-point bending tests, were carried out using the electro-hydraulic servo testing machine. The cubic compressive strength, splitting tensile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
2
2
Order By: Relevance
“…We also concluded from Figure 9 that our current study’s LWHFRC regression value is close to 0.8426, and the present study graph was similar to a normal concrete ACI 318-14 graph. However, the other normal concrete relationship graphs were higher than the current study graph [ 33 , 34 , 35 ].…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…We also concluded from Figure 9 that our current study’s LWHFRC regression value is close to 0.8426, and the present study graph was similar to a normal concrete ACI 318-14 graph. However, the other normal concrete relationship graphs were higher than the current study graph [ 33 , 34 , 35 ].…”
Section: Resultscontrasting
confidence: 61%
“…From Figure 10 , we also concluded that our present study’s LWHFRC regression value is nearly 0.8875, and the present study graph was too much higher than other graphs for normal concrete [ 33 , 34 , 35 ].…”
Section: Resultscontrasting
confidence: 57%
“…Granted that although concrete is not typically designed to resist direct tension, the knowledge of tensile strength is used to estimate the load under which cracking will develop. This is due to its influence on the formation of cracks and its propagation to the tension side of the reinforced concrete flexural members [25,26], hence the importance of tensile strength testing. This test was carried out using diameter 100 by 200 cylinders at 7 and 28 days using the split tensile strength test by crushing the cylinders longitudinally on a compressive strength test machine in line with the provisions of [27].…”
Section: Strength Testsmentioning
confidence: 99%
“…Furthermore, SAP play a key role in modulating the hydration process of concrete [20]. They possess the capability to absorb vast amounts of water and release it as the concrete starts drying, helping in the mitigation of crack formation [21][22][23][24]. The inclusion of SAP has been noted to considerably improve both the compressive and flexural strength of concrete, making it more adaptable for various architectural applications [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%